Extraction of peroxidase from apple peel waste mediated by tween 80 reverse micelle system. Issue 1 (December 2020) - Chen, Xiangyan; Fei, Jia; Peng, Xin; Meng, Yong; Yuan, Lu
Abstract: Plants peroxidase is an important class of oxidoreductases. It exists widely in plants, animals and microorganisms, capable of catalyzing the oxidation of H2 O2 phenols, vitamin C, nitrite, colorless dyes, indole and inorganic ion reaction. The reverse micelles extraction operation process is simple, continuous-operation, recyclable solvent, maintaining the native conformation of the protein. And it will not produce secondary pollution to the environment so that it has been gradually applied in the extraction and purification of the enzyme. Experimental operation of this paper was divided into the following two aspects: on the one hand, the selection of extraction technique and methods of detecting enzyme content and activity. We selected coomassie blue staining to determine enzyme content, while using ultraviolet spectrophotometry to resveratrol as a substrate for peroxidase activity assessment. On the other hand, the main aspect was how single factor affected reverse micelles extraction efficiency, including the aqueous phase pH, surfactant concentration and extraction time. By comparing difference of the recovery and purification of peroxidase between multiple different variables under same factors, we could get the optimum conditions: Tween 80 at a concentration of 0.30 mol/L, pH = 4.5, oscillation time of 20 min.